INTEGRATING ICT IN ENGLISH LANGUAGE LEARNING: A MULTI-STAKEHOLDER PERSPECTIVE FROM STUDENTS, LECTURERS, AND INSTITUIONAL STAKEHOLDERS IN HIGHER EDUCATION - Maya Marsevani; Desty Febria (English Study Program University of Pasir Pengaraian, 2026)
The integration of Information and Communication Technology (ICT) plays a crucial role in enhancing interactive and student-centered English language learning in higher education. However, limited studies have explored the combined perspectives of lecturers, students, and institutional stakeholders. This study aims to examine their perceptions, practices, and roles in ICT implementation at Batam International University, Indonesia. Using a qualitative case study design with triangulation, data were collected through questionnaires, semi-structured interviews, and classroom observations. The findings indicate that students view ICT positively, noting its impact on motivation, autonomy, and engagement, though digital literacy challenges remain. Lecturers recognize its pedagogical benefits but face constraints such as time, technical issues, and alignment with instructional practices. Stakeholders are crucial in providing institutional support, training, and infrastructure. The study highlights the need for a holistic approach to ICT integration, aligning pedagogical practices, technological readiness, and institutional policies. Strengthening digital literacy and promoting continuous professional development are essential for optimizing ICT use in English language learning.